A hospital based pilot study on Epstein-Barr virus in suspected infectious mononucleosis pediatric patients in India - Madhuravasal Krishnan Janani; Jambulingam Malathi; Andal Appaswamy; Nishi Rani Singha; Hajib Nariharirao Madhavan (Journal of Infection in Developing Countries)
Introduction: Infectious mononucleosis (IM) caused by the Epstein-Barr virus (EBV) is commonly diagnosed by detection of antibodies in the patient’s sera. Differentiation of acute from chronic and differential diagnosis of EBV-induced IM from IM-like syndrome caused by human cytomegalovirus (CMV) is important. The objective of this study was to standardize and use polymerase chain reaction (PCR) for diagnosis of EBV and evaluate it against enzyme-linked immunosorbent assay (ELISA). Methodology: ELISA for detection of IgM and IgG antibodies to viral capsid antigen (VCA) and PCR targeting the VCA and EBNA1 gene of EBV and mtrII gene of CMV were performed on180 peripheral blood samples collected from 180 patients with suspected IM. The analytical sensitivity of PCR was evaluated against that of ELISA. Results: Using the standard serological profile as the reference, the EBV-VCA gene was detected in 41 (95%) of 45 samples collected from patients with early primary infections, in 41 (54%) of 75 with recent primary infections, and in7 (17%) of 39 with past infections. The result of VCA PCR was statistically significant in virus detection during early or primary stage of infection. Nineteen (49%) EBV-seropositive samples were positive for CMV by PCR. All control samples tested negative for both VCA and EBNA1by PCR. Conclusions: VCA PCR is sensitive for the detection of EBV DNA in the early or primary stage of infection and can be considered a reliable method to rule out the cross-reactivity and differential diagnosis of EBV-induced IM from IM-like syndrome.